From independence to the U.S. Constitution : reconsidering the critical period of American history - Bradburn, Douglas, 1972-; Pearl, Christopher R., 1983- (Early American histories., 2022)
"This volume re-examines the 1780s in American history, a crucial period when the Revolutionary generation worked out new political, economic, and social parameters that came to define the subsequent trajectory of the United States"--